PERANCANGAN SISTEM INFORMASI PENDAFTARAN HAJI DAN UMRAH PADA KBIH IBNU AQIL MENGGUNAKAN METODE WATERFALL - Zainal Mustaqim; Edhi Prayitno (Journal of Innovation And Future Technology (IFTECH), 2024)
KBIH Ibnu Aqil is part of the Agus Salim Bogor Haji Foundation which operates in the field of training and guidance for Hajj and Umrah pilgrims. The registration system implemented by KBIH Ibnu Aqil is still carried out by the congregation having to come directly to the foundation, this is felt to make it less easy for the congregation to find out information regarding the details of the registration process, the costs incurred and also the departure schedule related to the implementation of the Hajj and Umrah. Furthermore, the process of creating the registration report takes a long time, because it is still done manually by recording it in stages. Therefore, with these problems, a web-based registration information system is needed to overcome problems in the current system, this aims to facilitate registration and dissemination of information. The research method used was direct observation and interviews with the admin and chairman of KBIH. Meanwhile, the software development method used is the waterfall method and the application creation uses CodeIgniter as a PHP framework, and the database uses MySQL. The expected results from designing a web-based Hajj and Umrah registration information system at KBIH Ibnu Aqil are expected to improve the services provided to pilgrims and become a solution to existing problems.